EFFECT OF FORTIFYING BY WHEY PROTEIN AND PROIOTIC BACTERIA ON PROPERTIES OF SOFT CHEESE DURING COLD STORAGE 1- EFFECT OF POWDERED AND CURD WHEY ON COAGULATION TIME AND CURD TENSION - Azhar Ibrahim shaker (Mesopotamia Journal of Agriculture, 2013)
Whey protein was used in the manufacture of soft cheese to compensate the fat flavor. The effect of whey powder or its precipitated proteins on coagulation time and curd tension. In first stage, whey powder was added at 1, 2, 3 and 4 % to the milk directly and heated at 90°c for 1 minute to precipitate whey protein. In the second stage, whey proteins were precipitated by acid and heating then added to pasteurized milk at 2, 4 and 6 %. Results showed that heating the milk had increased the coagulation time, while adding whey powder had reduced it according to the added percentages, but no as well as raw milk. Adding whey curd (proteins) resulted in increasing the coagulation time compared with raw and pasteurized milk samples. Nevertheless, the curd tension was reduced with the addition of whey powder and whey proteins with no significant effects were noticed among treatments.